The making of Southeast Asian nations state, ethnicity, indigenism and citizenship - Suryadinata, Leo (World Scientific Publishing Co.Pte Ltd., 2015)
The idea of the 'nation' is a Western concept which has been applied to Southeast Asia. It is a project which has been in progress since the last century but is still incomplete. Various theoretical frameworks which are associated with nation and nation-building in the Southeast Asian region have been briefly dealt with. The book aims to examine the making of the nations in Southeast Asia using both historical